2020
DOI: 10.3390/jfb11030058
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Scaffolds Containing Silver-Doped Hydroxyapatite with Antimicrobial Properties for Applications in Orthopedic and Dental Bone Surgery

Abstract: Preventing the development of osteomyelitis while enhancing bone regeneration is challenging, with relatively little progress to date in translating promising technologies to the clinic. Nanoscale hydroxyapatite (nHA) has been employed as a bone graft substitute, and recent work has shown that it may be modified with silver to introduce antimicrobial activity against known pathogens. The aim of this study was to incorporate silver-doped nHA into electrospun scaffolds for applications in bone repair. Silver-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Korkusuz et al 36 reported that parenteral antibiotics and surgical debridement alone or combined with antibiotic‐impregnated bone cement failed to eliminate infections and that locally implanted antibiotic‐impregnated hydroxyapatite succeeded in treating osteomyelitis in rats even when metal implants were not removed. With the advancing technology, nano‐sized systems have begun to find a place among biodegradable carriers 37 . It was suggested that nano‐sized calcium phosphate might be the most natural agent for local antibiotic transfer 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korkusuz et al 36 reported that parenteral antibiotics and surgical debridement alone or combined with antibiotic‐impregnated bone cement failed to eliminate infections and that locally implanted antibiotic‐impregnated hydroxyapatite succeeded in treating osteomyelitis in rats even when metal implants were not removed. With the advancing technology, nano‐sized systems have begun to find a place among biodegradable carriers 37 . It was suggested that nano‐sized calcium phosphate might be the most natural agent for local antibiotic transfer 38 .…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are mainly related to the form of the silver and long‐term accumulation of silver 22,23 . In recent years, double‐action silver‐added calcium phosphate combinations developed for the treatment of bone infections have been published 37,44 . Paterson et al 37 developed electrospun PCL scaffolds containing silver‐doped hydroxyapatite with antimicrobial properties and examined in‐vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This was addressed by modifying nanoscale HA with sliver, which is known to have antimicrobial properties, and combining with an electrospun scaffolds. As a proof-of-concept study this scaffold was shown to be non-toxic to rat BMSC and improved osteogenic differentiation capacity of cultured BMSC, while significantly reducing bacterial populations [ 86 ]. Using a similar concept, ZnO/nanocarbon modified fibrous scaffolds have demonstrated osteogenic and antibacterial properties, albeit in vitro [ 87 ].…”
Section: Skeletal Tissue Regeneration—advancements Over the Last Dmentioning
confidence: 99%
“…Silver nanorods incorporated within highly porous wollastonite scaffolds determined strong bactericidal effects while providing the favorable apatite-forming ability and good cytocompatibility with respect to osteoblast-like cells [ 326 ]. Composite freeze-thawed gelatin/alginate/PVA and electrospun PCL scaffolds embedded with a bactericidal concentration of silver-HAp nanoparticles showed suitable porosity and prolonged release metallic ions, with simultaneous favorable adhesion, proliferation and osteogenic potential on mammalian cells [ 327 , 328 ].…”
Section: Silver Nanoparticles For Tissue Engineeringmentioning
confidence: 99%